PENGELOLAAN PENDIDIKAN MENENGAH ATAS PASCA UNDANG-UNDANG PEMERINTAHAN DAERAH - Herman, Andi Akbar (Universitas Slamet Riyadi, 2019)
AbstractEducation is the constitutional right of every citizen, as mandated in the 1945 Constitution of the Republic of Indonesia, so that good management of education will support the progress of a nation. The attraction of government affairs in terms of education carried out by the central government to the district governments to the provincial regions actually further alienated public services. The type of research used in compiling this study is empirical legal research. The results showed that the management of education has implications for the ineffectiveness of the management of senior secondary education in Kolaka Utara district both from the aspect of budget management, management of facilities and infrastructure and management of human resources, no longer effective. This situation has made the provincial government have to establish a branch office in North Kolaka district to support administrative arrangements in the North Kolaka district.AbstrakPendidikan adalah hak konstitusional setiap warga negara, sebagaimana diamanatkan dalam Undang-Undang Dasar Negara Republik Indonesia Tahun 1945, sehingga pengelolaan pendidikan secara baik akan menunjang kemajuan sebuah bangsa. Tarik menarik urusan pemerintahan dalam hal pendidikan yang dilakukan oleh pemerintah pusat terhadap pemerintah daerah kabupaten ke daerah provinsi justru semakin menjauhkan pelayanan masyarakat. Jenis penelitian yang digunakan dalam menyusun penelitian ini adalah penelitian hukum empiris. Hasil penelitian menunjukkan bahwa pengelolaan pendidikan berimplikasi pada tidak berjalan efektifnya pengelolaan pendidikan menengah atas di kabupaten Kolaka Utara baik dari aspek pengelolaan anggaran, pengelolaan sarana dan prasarana serta pengelolaan sumber daya manusia, tidak lagi berjalan efektif. Keadaan tersebut membuat pemerintah provinsi harus membuat kantor ccabang dinas di kabupaten Kolaka Utara untuk menunjang pengurusan administrasi di daerah kabupaten Kolaka Utara.